A minimalist cache coherent MPSoC designed for FPGAs. (24th March 2015) - Tortato, Jorge; Hexsel, Roberto A.
We describe the design and VHDL implementation of a cache coherent MPSoC named minimalist cache coherent MPSoC (MCCM). The system comprises one to eight MIPS-I processors, coherent primary data caches, memory management units, memory controller and the interconnection. We present a detailed account of the implementation, focusing on the shared memory subsystem. A simple benchmark is used to assess the overall system functionality. We compared the size of our design to that of a LEON3-based multiprocessor and found that a four-core LEON3 system needs roughly the same amount of logic/state as a six to eight cores MCCM.